Early and dynamic detection of doxorubicin induced cardiotoxicity by myocardial contrast echocardiography combined with two-dimensional speckle tracking echocardiography in rats - Zhang, Jun; Li, Xin; Liu, Juan; Shang, Yongning; Tan, Lin; Guo, Yanli (Frontiers in Cardiovascular Medicine, 2023)
Background: Anthracycline-induced cardiotoxicity is a well-recognized adverse effect of chemotherapy. There are currently no clinical imaging techniques available to detect doxorubicin (DOX)-induced cardiotoxicity before functional decline. This study aimed to assess the feasibility of applying myocardial contrast echocardiography (MCE) for evaluation of early and dynamic cardiac changes in a DOX-induced cardiotoxicity rat model. Methods: Rat models of cardiotoxicity were generated by injecting rats with doxorubicin (2.5 mg/kg, once a week). All groups underwent ultrasonic examinations including standard echocardiography, 2D speckle tracking echocardiography (2D-STE) and MCE. Then all rats were sarcrificed immediately for histopathological evaluation. Results: Eight control rats and 32 doxorubicin-treated rats were included and classifed into treatment periods. Decreased quantitative parameters of myocardial perfusion myocardial blood flow (MBF) (control vs. group 1: 133.31 ± 20.23 dB/s vs. 103.35 ± 21.60 dB/s, P = 0.048) and β (control vs. group 2: 11.17 ± 1.48 /s vs. 7.15 ± 1.23 /s, P < 0.001) were observed after 2 and 4 weeks of treatment respectively, while left ventricular global strain (control vs. group 3: -23.67 ± 3.92 % vs. -16.01 ± 3.40 %, P = 0.002) decreased after 6 weeks of treatment and left ventricular ejection fraction (LVEF) (control vs. group 4: 82.41 ± 3.20 % vs.70.89 ± 9.30 %, P = 0.008) decreased after 8 weeks of treatment. The main histopathological features were myocardial vacuolization, interstitial fibrosis and decreased myocardial microvessel density. Conclusion: Compared with standard echocardiography and 2D-STE, MCE can accurately and non-invasive detect the changes of early myocardial perfusion, which shows the clinical potential for continuous and dynamic monitoring of DOX-induced cardiotoxicity in clinical practice.